Oxidative stress in relation to adenosine deaminase, nitric oxide, nitric oxide synthase and xanthine oxidase in oral cavity cancer - Ant, Ayca; Inal, Erdogan; Avci, Aslihan; Genc, Metin; Tuncel, Umit; Sencan, Ziya; Genc, Yasemin (The European Research Journal, 2018)
Inflammation and oxidative stress are considered as the main pathways in oral cavity carcinoma. The aim of this study was to evaluate the activity levels of adenosine deaminase (ADA), nitric oxide (NO), nitric oxide synthase (NOS), and xanthine oxidase (XO) in oral cavity carcinoma, to determine their potential roles in carcinogenesis with relation to oxidative stress.Methods. Seventeen patients with oral cavity cancer underwent surgery as the primary therapy, were consisted in the study. Resected oral cavity carcinoma tissues were compared with the adjacent tumor-free control tissues of the same patients; ADA, NO, NOS, XO activity levels were evaluated in terms of difference.Results. There is a significant increase of ADA activity in squamous cell cancer tissues, which indicates a difference between the normal and tumor tissues at enzyme levels (p